2022
DOI: 10.1038/s42005-022-01051-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemocytes in Drosophila melanogaster embryos move via heterogeneous anomalous diffusion

Abstract: Drosophila melanogaster hemocytes are highly motile cells that are crucial for successful embryogenesis and have important roles in the organism’s immunological response. Here we measure the motion of hemocytes using selective plane illumination microscopy. Every hemocyte cell in one half of an embryo is tracked during embryogenesis and analysed using a deep learning neural network. We show that the anomalous transport of the cells is well described by fractional Brownian motion that is heterogeneous in both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Interestingly, local (time resolved) anomalous exponents (and also local generalized diffusion coefficients) of individual hemocytes were found to exhibit oscillatory behaviour which could be a manifestation of a positive feedback loop between actin flows and maintenance of cell polarity [299,300] and/or similar periodic shape oscillations to those observed during the run-and-stop motions of T cells [301]. Upon their contact, we found that the hemocyte motion was synchronised, although their clear sense of directional motion was lost [74]. Contact of the cells inhibits their motion (a process of contact inhibitory locomotion) and the anomalous transport of cells continues to be synchronised in terms of the anomalous exponents, generalized diffusion coefficients, displacements, and velocities.…”
Section: Leukocytes/hemocytesmentioning
confidence: 65%
See 4 more Smart Citations
“…Interestingly, local (time resolved) anomalous exponents (and also local generalized diffusion coefficients) of individual hemocytes were found to exhibit oscillatory behaviour which could be a manifestation of a positive feedback loop between actin flows and maintenance of cell polarity [299,300] and/or similar periodic shape oscillations to those observed during the run-and-stop motions of T cells [301]. Upon their contact, we found that the hemocyte motion was synchronised, although their clear sense of directional motion was lost [74]. Contact of the cells inhibits their motion (a process of contact inhibitory locomotion) and the anomalous transport of cells continues to be synchronised in terms of the anomalous exponents, generalized diffusion coefficients, displacements, and velocities.…”
Section: Leukocytes/hemocytesmentioning
confidence: 65%
“…For a large class of HAT systems (containing anomalous yet Brownian diffusion [115,116,118]), G(x, t|D) is given by a Gaussian distribution and thus non-Gaussian tails for P (x, t) are due to the distribution of diffusion coefficients, P (D). Homogeneous diffusion with a single value for the diffusion coefficient, 74,115,118,123]. The Gamma probability distribution of diffusion coefficients (γ and β are constants), p(D) ∼ D β−1 exp(−γD), produces Laplacian tails in the P (x, t) [124].…”
Section: Superstatistical Models: Anomalous Diffusion Caused By Ensem...mentioning
confidence: 99%
See 3 more Smart Citations